Recommendations of the AGG (Obstetrics Working Group, Section for Maternal Diseases) for the Management of Anemia in Pregnancy – Part 1 (Iron Deficiency Anemia) - Hamza, Amr Sherif; Kehl, Sven; Bittenbring, Jörg; Kranke, Peter; Pecks, Ulrich; Doubek, Klaus; Rehn, Monika (Geburtshilfe und Frauenheilkunde, 2025)
These recommendations by the AGG (Committee for Obstetrics, Department of Maternal Diseases) on how to treat iron-deficiency anemia during pregnancy aim to improve the diagnosis and management of iron-deficiency anemia in pregnancy.The task force members developed the following recommendations and statements based on the current literature. Recommendations were adopted after the members of the working group achieved consensus.This article gives an insight into the diagnosis and management of iron-deficiency anemia in pregnancy and provides recommendations on its treatment.Ziel dieser von der AGG (Arbeitsgemeinschaft Geburtshilfe, Sektion Maternale Erkrankungen) entwickelten Empfehlungen zur Behandlung der Eisenmangelanämie in der Schwangerschaft ist, die Diagnostik und Behandlung der Eisenmangelanämie während der Schwangerschaft zu verbessern.Die im Folgenden aufgeführten Empfehlungen und Statements der Arbeitsgruppe basieren auf einer Durchsicht der aktuellen Literatur. Die Empfehlungen wurden nach einem Konsensverfahren der Arbeitsgruppe angenommen.Es werden hier Einblicke in die Diagnose und den Umgang mit Eisenmangelanämie in der Schwangerschaft sowie Empfehlungen zur deren Behandlung gegeben.
Keywords: anemia; iron deficiency; iron deficiency anemia